Pengaruh Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderating pada Perusahaan Sektor Consumer Non-Cyclicals - Nadilla Silva Fitri; Elfiswandi .; Muhammad Pondrinal (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This research is motivated by the importance of firm value as an indicator of market perception of company performance and prospects, particularly in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2020–2024 period. Fluctuations in firm value indicate the presence of internal factors that potentially influence investor assessments, including profitability and capital structure. Furthermore, firm size is considered a moderating variable that is thought to strengthen or weaken the relationship between these variables. This study aims to analyze the effect of profitability and capital structure on firm value, with firm size as a moderating variable. This study uses a quantitative approach with an associative research type. The study population is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was determined using a purposive sampling technique, resulting in 39 companies with a total of 195 observations. The data used are secondary data in the form of annual financial reports obtained through documentation from the official Indonesia Stock Exchange website. Data analysis was performed using the panel data regression method using the EViews 10 application. The results show that profitability has no significant effect on firm value, while capital structure has a significant effect on firm value. Firm size has been shown to weaken the effect of profitability but strengthen the influence of capital structure on firm value. This finding indicates that appropriate capital structure management is a crucial factor in increasing firm value.